1996
DOI: 10.1161/01.cir.94.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene Polymorphism Is Associated With Carotid Arterial Wall Thickness in Non–Insulin-Dependent Diabetic Patients

Abstract: The D allele of the ACE gene may be a risk factor for the development of wall thickening of the carotid but not the femoral artery in NIDDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…A lack of association between ACE gene polymorphism and carotid IMT has also been demonstrated in a low-risk population (Dessi-Fulgheri et al 1995). On the other hand, an association of polymorphisms of the ACE gene and IMT was reported in specific populations, such as noninsulin-dependent diabetes mellitus (NIDDM) patients (Hosoi et al 1996), hemodialysis patients (Nergizoglu et al 1999), and hypertensive patients (Jeng 2000). These findings suggest risk factor-genotype interactions of the ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of association between ACE gene polymorphism and carotid IMT has also been demonstrated in a low-risk population (Dessi-Fulgheri et al 1995). On the other hand, an association of polymorphisms of the ACE gene and IMT was reported in specific populations, such as noninsulin-dependent diabetes mellitus (NIDDM) patients (Hosoi et al 1996), hemodialysis patients (Nergizoglu et al 1999), and hypertensive patients (Jeng 2000). These findings suggest risk factor-genotype interactions of the ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…2 The same limitations appear to apply to the small number of studies that have examined the association of ACE I/D polymorphism with carotid IMT, and reported similarly heterogeneous findings (summarized in Table 5). [11][12][13][14][15][16] Four of these studies found a positive association, 11,14 -16 although this was only after a quarter of subjects on drug treatment were excluded from analysis in 1 small study 11 and only among nonsmokers in another study 16 ; 2 other studies 12,13 showed no association of the D allele with carotid wall thickening or disease despite that it conferred an increased risk of lacunar stroke in 1 study. 13 None of the studies were able to demonstrate a relationship between the D allele and carotid plaque or stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] We therefore decided to test for the association of carotid IMT and ACE I/D polymorphism in the Perth Carotid Ultrasound Disease Assessment Study (CUDAS). The latter consisted of 1111 male and female subjects, aged 27 to 77 years, randomly selected from the Perth community population, all of whom had high-resolution bilateral B-mode carotid ultrasound examination and ACE I/D gene polymorphism determined as part of a detailed risk factor assessment.…”
mentioning
confidence: 99%
“…Then the right side was used as representative because the coefficient of variation was significantly lower than in the left side (right vs left side: 3.4 vs 4.2%). Using digitized still images of the arteries taken during scanning, IMT was measured in the far wall of the right CCA at sites of the most advanced atherosclerotic lesions, identified as diffuse and continuous projections with the greatest distance between the lumen -intimal interface and the media -adventitial interface but without atherosclerotic plaque, which was defined as localized lesions of thickness $ 2.0 mm (35,36). These interfaces were manually traced and the mean value calculated as the mean of at least three still images obtained from the same section of the CCA.…”
Section: Measurement Of Cca Imtmentioning
confidence: 99%